MicroRNA‐31 is required for astrocyte specification. Issue 5 (30th January 2018) - Meares, Gordon P.; Rajbhandari, Rajani; Gerigk, Magda; Tien, Chih‐Liang; Chang, Chenbei; Fehling, Samuel C.; Rowse, Amber; Mulhern, Kayln C.; Nair, Sindhu; Gray, G. Kenneth; Berbari, Nicolas F.; Bredel, Markus; et al.
Abstract: Previously, we determined microRNA‐31 (miR‐31) is a noncoding tumor suppressive gene frequently deleted in glioblastoma (GBM); miR‐31 suppresses tumor growth, in part, by limiting the activity of NF‐κB. Herein, we expand our previous studies by characterizing the role of miR‐31 during neural precursor cell (NPC) to astrocyte differentiation. We demonstrate that miR‐31 expression and activity is suppressed in NPCs by stem cell factors such as Lin28, c‐Myc, SOX2 and Oct4. However, during astrocytogenesis, miR‐31 is induced by STAT3 and SMAD1/5/8, which mediate astrocyte differentiation. We determined miR‐31 is required for terminal astrocyte differentiation, and that the loss of miR‐31 impairs this process and/or prevents astrocyte maturation. We demonstrate that miR‐31 promotes astrocyte development, in part, by reducing the levels of Lin28, a stem cell factor implicated in NPC renewal. These data suggest that miR‐31 deletions may disrupt astrocyte development and/or homeostasis. Main Points: MicroRNA‐31 (miR‐31) promotes astrocyte development by downregulating stem cell factor Lin28.